THE COMMODIFICATION OF ACADEMIC RESEARCH AND THE KNOWLEDGE SOCIETY - MARIA CERNAT (Challenges of the Knowledge Society)
The knowledge society is best defined as the society where production, distribution and use of knowledge play the central role in the social matrix. The possession of technological means of production has been replaced be the possession of useful knowledge, and most theorists embrace this change thinking it could offer us hope for a better future. But does it really contribute to the development of a better society? The main objective of my article is to offer a realistic answer to this question. The perpetuation of the capitalistic way of production in the academic world leads us to the situation where ideas and scientific articles are being commodified. In theory, the knowledge society is build on the idea of producing, disseminating and using information for the well being of the people. I claim that this is a very naïve perspective on how our current knowledge society is actually functioning. Since information is so easy to transfer one could expect that all the members of the society could benefit form it. As my article will show, this is not in fact the case. Not everybody is able to produce and use knowledge. Since what we are experiencing is the commodification of academic articles only few people are able to produce and use knowledge. This way the knowledge society becomes a closed society where only a privileged financial elite has access to the latest academic research.